On Romanian Imagery and Artistic Heritage from a Transdisciplinary Perspective - Ana – Magdalena Petraru (Anastasis: Research in Medieval Culture and Art)
Book review Corin Braga (coord. general), Enciclopedia imaginariilor din România, vol. V, Liviu Malița (coord.), Imaginar și patrimoniu artistic/ The Encyclopedia of Romanian Imaginaries, vol V, Imaginary and Artistic Heritage, Polirom Publishing House, 2020, 504 pages